A quasi-experimental study to mobilize rural low-income communities to assess and improve the ecological environment to prevent childhood obesity - Paula Peters; Abby Gold; Angela Abbott; Dawn Contreras; Ann Keim; Renee Oscarson; Sandra Procter; Valentina Remig; Carol Smathers; Amy R. Mobley (BMC, 2016)
Abstract Background The Ecological Model of Childhood Overweight focuses on characteristics that could affect a child's weight status in relation to the multiple environments surrounding that child. A community coaching approach allows community groups to identify their own strengths, priorities and identity. Little to no research currently exists related to community-based efforts inclusive of community coaching in creating environmental change to prevent childhood obesity particularly in rural communities. Methods A quasi-experimental study will be conducted with low-income, rural communities (n = 14) in the North Central region of the United States to mobilize capacity in communities to create and sustain an environment of healthy eating and physical activity to prevent childhood obesity. Two rural communities within seven Midwestern states (IN, KS, MI, OH, ND, SD, WI) will be randomly assigned to serve as an intervention or comparison community. Coalitions will complete assessments of their communities, choose from evidence-based approaches, and implement nutrition and physical activity interventions each year to prevent childhood obesity with emphasis on policy, system or environmental changes over four years. Only intervention coalitions will receive community coaching from a trained coach. Outcomes will be assessed at baseline, annually and project end using previously validated instruments and include coalition self-assessments, parental perceptions regarding the built environment, community, neighborhood, and early childhood environments, self-reflections from coaches and project staff, ripple effect mapping with coalitions and, final interviews of key stakeholders and coaches. A mixed-methods analysis approach will be used to evaluate if Community Coaching enhances community capacity to create and sustain an environment to support healthy eating and physical activity for young children. ANOVA or corresponding non-parametric tests will be used to analyze quantitative data relating to environmental change with significance set at P < .05. Dominant emergent themes from the qualitative data will be weaved together with quantitative data to develop a theoretical model representing how communities were impacted by the project. Discussion This project will yield data and best practices that could become a model for community development based approaches to preventing childhood obesity in rural communities.